Friction and wear properties of graphene oxide/ultrahigh‐molecular‐weight polyethylene composites under the lubrication of deionized water and normal saline solution. Issue 1 (12th August 2013) - An, Yingfei; Tai, Zhixin; Qi, Yuanyuan; Yan, Xingbin; Liu, Bin; Xue, Qunji; Pei, Jinying
ABSTRACT Ultrahigh‐molecular‐weight polyethylene (UHMWPE) and UHMWPE composites reinforced with graphene oxide (GO) were successfully fabricated through a new step of liquid‐phase ultrasonic dispersion, high‐speed ball‐mill mixing, and hot‐pressing molding technology. When the GO/UHMWPE composites were lubricated with deionized water (DW) and normal saline (NS) solution, their friction and wear properties were investigated through sliding against ZrO2. The worn surface and wear volume losses of these composites were studied with scanning electron microscopy, X‐ray photoelectron spectroscopy, and a Micro‐XAM 3D non‐contact surface profiler. The results show that the microhardness of the GO/UHMWPE composites was improved by 13.80% and the wear rates were decreased by 19.86 and 21.13%, whereas the depths of the scratches were decreased by 22.93 and 23.77% in DW and NS lubricating conditions, respectively. © 2013 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2014, 131, 39640.